Inositol - why should it be in the spotlight for women in a reproductive age? - Tomaszuk, Sebastian; Wąsik, Karolina; Wojtuś, Magda (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Inositol exists in the form of nine isomers, two of which are dominant - myo-inositol (MI) and D-chiro-inositol (DCI). It is a naturally occuring sugar involved in many biological pathways. Due to its insulin-sensitizing, anti-inflammatory and antioxidant properties, inositol has been suggested as a novel treatment agent in prevention and treatment of reproductive disorders. The paper presents currently available data regarding the impact of oral supplementation of inositol for fertility of women and men, reproductive outcomes among subfertile women with polycystic ovarian syndrome (PCOS) and its effectiveness on preventing and treating gestational diabetes mellitus (GDM). Material and methods of research: The search was conducted using PubMed and Google Scholarship databases available to November 2023. Results: Although the evidence is still insufficient, it is suggested that inositol may be beneficial for subfertile women, also those undergoing assisted reproductive techniques and in vitro fertilization. Moreover inositol can positively influence sperm quality. Myoinositol supplementation was also effective and safe for pregnant women with GDM and their children. In these women lower HOMA-IR (Homeostatic Model Assessment – Insulin Resistance) and reduction of fetal macrosomia were observed. Myoinositol also seems to be favorable for overweight or obese women in GDM prevention and treatment. Current findings indicate the positive impact for hormonal changes and restoration in menstrual cyclicity in women with PCOS, improving reproductive disorders in these patients. Conclusions: Overall, although findings are encouraging, further trials for this promising intervention are still required to support oral supplementation of inositol.